Effect of dispersants of multi-walled carbon nanotubes on cellular uptake and biological responses - Haniu H (Dove Medical Press, 2011)
Hisao Haniu1, Naoto Saito2, Yoshikazu Matsuda3, Yoong-Ahm Kim4, Ki Chul Park1, Tamotsu Tsukahara5, Yuki Usui6, Kaoru Aoki7, Masayuki Shimizu7, Nobuhide Ogihara7, Kazuo Hara7, Seiji Takanashi7, Masanori Okamoto7, Norio Ishigaki7, Koichi Nakamura7, Hiroyuki Kato71Institute of Carbon Science and Technology, Shinshu University, Matsumoto, Nagano, Japan; 2Department of Applied Physical Therapy, Shinshu University School of Health Sciences, Matsumoto, Nagano, Japan; 3Clinical Pharmacology Educational Center, Nihon Pharmaceutical University, Ina-machi, Saitama, Japan; 4Faculty of Engineering, Shinshu University, Nagano-shi, Nagano, Japan; 5Department of Integrative Physiology and Bio-System Control, Shinshu University School of Medicine, Matsumoto-shi, Nagano, Japan; 6Research Center for Exotic Nanocarbons, Shinshu University, Matsumoto, Nagano, Japan; 7Department of Orthopedic Surgery, Shinshu University School of Medicine, Matsumoto, Nagano, JapanAbstract: Although there have been many reports about the cytotoxicity of multi-walled carbon nanotubes (MWCNTs), the results are still controversial. To investigate one possible reason, the authors investigated the influence of MWCNT dispersants on cellular uptake and cytotoxicity. Cytotoxicity was examined (measured by alamarBlue® assay), as well as intracellular MWCNT concentration and cytokine secretion (measured by flow cytometry) in human bronchial epithelial cells (BEAS-2B) exposed to a type of highly purified MWCNT vapor grown carbon fiber (VGCF®, Showa Denko Kabushiki-gaisha, Tokyo, Japan) in three different dispersants (gelatin, carboxylmethyl cellulose, and 1,2-dipalmitoyl-sn-glycero-3-phosphocholine). The authors also researched the relationship between the intracellular concentration of MWCNTs and cytotoxicity by using two cell lines, BEAS-2B and MESO-1 human malignant pleural mesothelioma cells. The intracellular concentration of VGCF was different for each of the three dispersants, and the levels of cytotoxicity and inflammatory response were correlated with the intracellular concentration of VGCF. A relationship between the intracellular concentration of VGCF and cytotoxic effects was observed in both cell lines. The results indicate that dispersants affect VGCF uptake into cells and that cytotoxicity depends on the intracellular concentration of VGCF, not on the exposed dosage. Thus, toxicity appears to depend on exposure time, even at low VGCF concentrations, because VGCF is biopersistent.Keywords: multi-walled carbon nanotube, cytotoxicity, intracellular concentration, dispersant, cytokine secretion